Youth and weapons: Patterns, individual and neighborhood correlates of violent crime arrests in Miami-Dade County, Florida. (September 2020) - Moise, Imelda K.
Abstract: This study uses arrest data from the Miami-Dade County Police Department (n = 13 districts) for 2014–2017 to identify census tracts in which weapon violence arrests among young people aged 10–24 is high, and models area-level predictors of the total number of violent weapons crimes by census tract (greenness and socioeconomic status indices, population density and weapon dealers), after adjusting for arrestee-level factors (age, race and gender). Combined, handguns and firearms accounted for 23.2% (n = 1330) of all arrests (including murder and non-negligent manslaughter, rape, robbery, and aggravated assault). Arrests for weapon -related violent crime are concentrated in census tracts located in the north and south neighborhoods of Miami-Dade County. Findings indicate that arrestee factors and a neighborhood greenness index are more important than population density, weapon dealers and poverty in predicting arrests for weapon-related violent crime at the census tract level. Highlights: Weapon violence arrests are identified using police data. Arrestee factors and a neighborhood index are more salient. Handguns and firearms accounted for 23.2% of all arrests involving a weapon.